First Year Course-Based Undergraduate Research Experience (CURE) Using the CRISPR/Cas9 Genome Engineering Technology in Zebrafish - Bhatt, Jay M. (J Microbiol Biol Educ, 2017)
Genetic analysis in model systems can provide a rich context for conceptual understanding of gene structure, regulation, and function. With an intent to create a rich learning experience in molecular genetics, we developed a semester-long course-based undergraduate research experience (CURE) using the CRISPR-Cas9 gene editing system to disrupt specific genes in the zebrafish. The course was offered to freshman students; nine students worked in four groups (two to three members per group) to design, synthesize, and test the nuclease activity of the CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats)/sgRNAs for targeted disruption of specific genes in the zebrafish. Each group worked with a gene with an already known mutant phenotype that can be visually scored and a gene that had not been studied in zebrafish previously. Embedded in the course were a series of workshop-styled units or tutorials, including tours to core facilities. The focus was on introducing and developing skills that could be accommodated within the span of a semester. Each group successfully cloned at least one plasmid-encoding CRISPR/sgRNA template, visually analyzed injected embryos, and performed genotyping assays to detect CRISPR-Cas9 activity. In-class discussions, a final end-of-semester written test, and group oral presentations were assessed for an understanding of the CRISPR-Cas9 system, application of the CRISPR-Cas9 system as a gene manipulation tool, and experimental methods used to create plasmid vectors and synthesize sgRNA. In addition, poster presentations were evaluated by faculty, graduate students, and senior undergraduate students at a University research exposition. Self-reflections in the form of group conversations were video recorded. All students (9/9) distinctly showed learning gains after completing the activity, but the extent of the gains was variable, as seen from results of a written test and poster presentation assessment. Qualitative analysis of evaluations and self-reporting data indicated several gains, suggesting that all students found many aspects of the CURE valuable and gained project-specific (conceptual) and transferrable skills (science process and science identity).